A Rare Case of Ruptured Tailgut Cyst Leading to Carcinomatosis - Samir Atiya; Adam Horn; Whitney Wedel; Nicholas Lintel (Hindawi Limited, 2023)
Tailgut cysts are congenital cysts arising in the retrorectal space. They are thought to be benign with variable malignancy risks. We report a case with previous surgical intervention decades prior that had undergone a tailgut cyst excision with surgical complications leading to carcinomatosis. An elderly female (70s) presented with tailbone/pelvic pain. She underwent cyst excision that was complicated by an intraoperative rupture. The cyst was pathologically proven to be a tailgut cyst with adenocarcinoma. She presented 13 months postoperatively to the emergency department with worsening abdominal pain. Imaging was concerning for diffuse omental nodules and narrowing of the proximal sigmoid colon. She was not deemed to be a surgical candidate and was transitioned to hospice care, where she passed away shortly afterward. This case report highlights the utility of complete excision of tailgut cysts and possible complications.